Respuesta :
Answer:
D
Step-by-step explanation:
x² + 7x + 12
to find the roots equate the expression to zero
x² + 7x + 12 = 0
Consider the factors of the constant term (+ 12) which sum to give the coefficient of the x- term (+ 7)
the factors are + 3 and + 4 , since
3 × 4 = 12 and 3 + 4 = 7 , then
(x + 3)(x + 4) = 0 ← in factored form
equate each factor to zero and solve for x
x + 3 = 0 ⇒ x = - 3
x + 4 = 0 ⇒ x = - 4
Answer:
D -3, -4.
Step-by-step explanation:
x^2 + 7x +12 = 0
12 = 3*4 and 7 = 3 + 4 so we write:
(x + 3)(x + 4) = 0
x + 3 = 0 , x + 4 = 0
So x = -3, -4.